Sub‑4 nm Nanodiamonds from Graphene-Oxide and Nitrated Polycyclic Aromatic Hydrocarbons at 423 K - Shen, Yuting; Su, Shi; Zhao, Wen; Cheng, Shaobo; Xu, Tao; Yin, Kuibo; Chen, Linjiang; He, Longbing; Zhou, Yilong; Bi, Hengchang; Wan, Shu; Zhang, Qiubo; et al. (ACS nano, 2021)
Nanodiamonds are interesting materials from the point of view of their biocompatibility and their chemical, spectroscopic, and mechanical properties. Current synthetic methods for nanodiamonds involve harsh environments, which are potentially hazardous in addition to being expensive. We report a low-temperature (423 K) hydrothermal approach to form nanodiamonds by using graphene-oxide or nitrated polycyclic aromatic hydrocarbons (naphthalene, anthracene, phenanthrene, or pyrene) as a starting material. The reaction products contain single-crystalline or twinned nanodiamonds with average diameters in the 2–3 nm range. Theoretical calculations prove that, at the nanoscale, sub-4 nm nanodiamonds may adopt a structure that is more stable than graphene-oxide and nitrated polycyclic aromatic hydrocarbons. Our findings show that sp 2 carbon in the polycyclic aromatic precursor can be converted to sp 3 carbon under unexpectedly moderate temperature conditions by using nanoscale precursors and thus offer a low-temperature approach for the synthesis of sub-4 nm nanodiamonds.